Influencing OCB in Teachers and Staff at MAN Mataram - eka andini (Innovative Pedagogy and Education Studies, 2024)
This study examines the factors influencing Organizational Citizenship Behavior (OCB) among teachers and educational staff at Madrasah Aliyah Negeri (MAN) in Mataram, Indonesia. OCB, defined as voluntary behaviors that contribute to organizational effectiveness without formal rewards, plays a critical role in enhancing institutional performance, collaboration, and student outcomes. Using a quantitative descriptive approach, the research identifies job satisfaction, leadership style, organizational culture, perceived organizational justice, and intrinsic motivation as key determinants of OCB. Findings reveal that 96.8% of respondents exhibit moderate to very high levels of OCB, indicating a generally positive organizational culture. However, challenges such as excessive workloads, lack of recognition, and limited professional development hinder optimal OCB levels. The study also highlights the unique influence of Islamic values in fostering discretionary behaviors, emphasizing the importance of aligning organizational practices with cultural and religious principles. Recommendations include strengthening transformational leadership, enhancing job satisfaction, ensuring fairness in reward systems, and fostering a collaborative work environment. By addressing these factors, MAN Mataram can improve institutional effectiveness and contribute to the broader goal of enhancing the quality of education in Indonesia. This research provides valuable insights for policymakers and educational stakeholders seeking to optimize human resource management and OCB in Islamic educational institutions.